EVALUASI PROGRAM TUNJANGAN PROFESI GURU DI SMP NEGERI KABUPATEN KENDAL - Yantono, Akhmad (Universitas Kristen Satya Wacana, 2016)
This study aimed to evaluate the level of achievement of teachersâ professional allowance goal in SMP Negeri 1 Pageruyung Kendal. This study useds a goal-oriented evaluation models developed by Ralph Winfred Tyler. Data were collected through interviews, questionnaires, observation, documentation and triangulation to ensure the validity of the data. Source of data was from the principal, teachers and students. Data were analyzed using qualitative analysis. The results showed that teachersâ professional allowance in SMP Negeri 1 Pageruyung: 1) has been able to raise the dignity of teachers, although the elements of scientific research has not been done by all teachers, and done only by one teacher. 2) has been able to improve the competence of teachers, although the elements of time management in the classroom has not been effective; the element of teachers questioning skill was not maximum; and the elements of evaluation, assessment tools have not been developed in accordance with the purpose of learning. 3) have not been able to advance the teachers professional because the teachers thoughts has not been communicated yet in the environment of the school and scientific forums. 4) has been able to improve the quality of learning, although in the assessment, teachers have not provided written comments on the test results, and has not given an assignment to write or read the related materials that have been learned. 5) has been able to improve the quality education services for learners.